Analisis perbandingan harga saham PT. Bank Rakyat Indonesia Syariah, TBK sebelum dan sesudah merger menjadi PT. Bank Syariah Indonesia, TBK. - Budi Prijanto; Nadia Damayanti; Agustin Rusiana Sari (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
In order to achieve business efficiency so that it becomes more competitive and more profitable, companies often carry out business mergers as a form of expansion. If the profit achieved by the company is higher, it can encourage an increase in its stock price, this is in accordance with fundamental rules. The purpose of this study was to examine whether there is a difference between the stock prices of PT. Bank Rakyat Indonesia Syariah Tbk before and after the merger into PT. Bank Syariah Indonesia Tbk. This research is classified as a comparative study, where the data used is stock price data within a time frame of 25 days before and after the merger. The analytical technique used is the Wilcoxon Signed Ranks Test. The conclusion of this study is that between the stock prices of PT. Bank Rakyat Indonesia Syariah before and after the merger into PT. Bank Syariah Indonesia Tbk there are significant differences. The difference that occurs shows that the stock price after the merger is higher than before the merger.